(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2016)
Review of Baroni, Raphaël and Françoise Revaz, eds. Narrative Sequence in Contemporary Narratology. Columbus: Ohio State University Press, 2016.